PROFESSIONAL VALORIZATION AND MENTAL HEALTH: A SITUATIONAL ANALYSIS IN THE MILITARY POLICE OF TOCANTINS (PMTO) - Cavalcante , Elio Chaves; Borges Sobrinho, Cléber José (Seven Editora, 2025)
This study analyzes the relationship between professional valorization and the mental health of military police officers in the state of Tocantins, seeking to understand how institutional policies influence well-being and functional performance. The general objective is to analyze the relationship between professional valorization and the mental health of military police officers in the State of Tocantins. The research adopts a qualitative and quantitative approach, based on a literature review and documentary analysis of programs and policies implemented by the Military Police of Tocantins (PMTO). The results show that work overload, irregular schedules, hierarchical conflicts, and structural limitations negatively affect the psychological health of police officers. Conversely, training initiatives, institutional recognition, and psychosocial support contribute to strengthening resilience and professional satisfaction. In conclusion, the general objective was achieved, and it is inferred that the effective integration of these policies is essential for consolidating an organizational culture grounded in care, recognition, and institutional efficiency. DOI: https://doi.org/10.56238/sevened2025.040-003